2006
DOI: 10.1111/j.1439-0485.2006.00080.x
|View full text |Cite
|
Sign up to set email alerts
|

Photoacclimation of the invasive alga Caulerpa racemosa var. cylindracea to depth and daylight patterns and a putative new role for siphonaxanthin

Abstract: The introduced green alga Caulerpa racemosa var. cylindracea grows along a broad depth range (from very shallow to 60 m depth) in the Mediterranean basin. In the present work, the photoacclimation capacity of this invasive variety was investigated in summer, the season of its maximum spread. Natural populations from the Gulf of Naples (Italy) were analyzed for photoresponse on two scales of light variability: a spatial scale (at three stations along a depth gradient, from 0.3 to 20 m depth) and a temporal scal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
49
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 51 publications
3
49
0
1
Order By: Relevance
“…However, the photosynthetic responses observed in this study are in good agreement with general metabolic strategies used by sublittoral macroalgae to optimize light use and productivity under variable light conditions (Markager and Sand-Jensen, 1992;Kirk, 1994;Pérez-Lloréns et al, 1996;Gómez et al, 1997;Lobban and Harrison, 1997;Gómez, 2001). Furthermore, our results are highly consistent with differences in photosynthetic behaviour reported by other studied Mediterranean populations of C. racemosa between shallow and deep habitats (Raniello et al, 2006). Importantly, the authors of these studies also interpreted there results as being due to photoacclimation.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…However, the photosynthetic responses observed in this study are in good agreement with general metabolic strategies used by sublittoral macroalgae to optimize light use and productivity under variable light conditions (Markager and Sand-Jensen, 1992;Kirk, 1994;Pérez-Lloréns et al, 1996;Gómez et al, 1997;Lobban and Harrison, 1997;Gómez, 2001). Furthermore, our results are highly consistent with differences in photosynthetic behaviour reported by other studied Mediterranean populations of C. racemosa between shallow and deep habitats (Raniello et al, 2006). Importantly, the authors of these studies also interpreted there results as being due to photoacclimation.…”
Section: Discussionsupporting
confidence: 82%
“…deep populations in winter: Cebrian and Ballesteros, 2009). However, our knowledge of the photoacclimative capacity of Mediterranean populations of C. racemosa is sparse at best (Raniello et al, 2004(Raniello et al, , 2006. Raniello et al (2004Raniello et al ( , 2006 reported interesting data showing how C. racemosa is able to re-organize its photosynthetic pigment system in response to varying light conditions caused by depth gradients, seagrass canopies, and daily and seasonal cycles.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…a larger photosynthetic efficiency at 20 than at 5 m depth. A similar pattern has been described for other Caulerpa species, such as Caulerpa racemosa in the Mediterranean Sea (Raniello et al 2006, BernardeauEsteller et al 2011. Not only deep-water (20 m depth) thalli of C. prolifera are more adapted to low irradiances: this alga also showed short-term acclimation under varying light regimes, i.e.…”
Section: Discussionmentioning
confidence: 58%